COMPARISON OF MEASURED AND CALCULATED CONTROL ROD REACTIVITY OF THE RSG-GAS CORE - T. Surbakti; W. Luthfi; Purwadi Purwadi; D. Hartanto (GANENDRA Majalah IPTEK Nuklir, 2021)
COMPARISON OF MEASURED AND CALCULATED CONTROL ROD REACTIVITY OF THE RSG-GAS CORE. The reactivity worth and a calibration curve of control rods are important physical parameters on account of the nuclear safety of the RSG-GAS reactor core. Reactivity characteristics of control rods must be determined not only, but also in the first criticality and also after any substantial changes in the reactor core. The required time to measure the reactivity worth by various methods depends mostly on the quality of the reactivity measurement devices. The rod-insertion method has some specific advantages which make such compensation unnecessary while yielding both integral and differential reactivity worth curves, as well as total reactivity worth. In this study, the total control rod worth of RSG-GAS is calibrated experimentally using a rod-insertion method to verify calculation results for the new core configuration. Calculations were done by diffusion and Monte Carlo methods using Batan-3DIFF and MCNP5 codes. Total control rod reactivity worth of the control rod is obtained 17.54 $,  17.03 $, and 17.87 $ by experiment,  Batan-3DIFF, and MCNP5 calculations, respectively. The relative difference between the experimental and calculated values of control rod reactivity worth is about 3.0 %, which indicates a good agreement between the applied experimental method and calculation.